2017
DOI: 10.1038/pr.2017.194
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between infancy growth rate and the onset of puberty in both genders

Abstract: BackgroundIn this study, we examined the hypothesis that weight gain and linear growth during the first years of life influence the onset of puberty both in girls and in boys.MethodsA cohort of 157 healthy children, aged 6-9 years, was evaluated and their growth patterns were analyzed retrospectively. Repeated measures mixed model was used to examine the longitudinal anthropometric data.ResultsGirls with pubertal signs were heavier than their peers starting at 9 months of age (P=0.02), and the difference becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“… 9 Other studies have shown that altered growth patterns during childhood may be associated with pubertal onset. 10 , 11 Although the biological mechanisms have yet to be fully elucidated, faster growth could alter the early hormonal milieu and program the age at onset and rate of progression through puberty. 12 Early growth may also be a marker of upstream exposures, such as environmental chemicals or excess nutrition, that are also associated with earlier pubertal onset.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Other studies have shown that altered growth patterns during childhood may be associated with pubertal onset. 10 , 11 Although the biological mechanisms have yet to be fully elucidated, faster growth could alter the early hormonal milieu and program the age at onset and rate of progression through puberty. 12 Early growth may also be a marker of upstream exposures, such as environmental chemicals or excess nutrition, that are also associated with earlier pubertal onset.…”
Section: Introductionmentioning
confidence: 99%
“…It helps clinicians anticipate mandibular growth patterns and assess bone maturity. Studies related to growth patterns and early maturity in children have demonstrated variation among the sexes [ 25 ]. Several radiographic methods have been used to predict the timing of pubertal growth spurt as part of routine diagnostics, but repeated radiation exposure raises ethical concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, besides genotype, environment and season, management, and physiological determinants (Foster, Yellon & Olster, 1985;Chenoweth & Lorton, 2014;Gobello, 2014), body energy reserves are one major factor contributing to normal onset and progress of puberty. Adequate nutrition is known from human medicine to play a permissive role in puberty attainment; undernutrition or poor body condition such as extreme low adiposity causes delay in puberty onset (Aydin et al, 2017). Our data confirmed the hypothesis that body weight had a permissive role, besides age, for puberty onset, which is also similar to previous studies that assessed a relationship between age and body weight for the attainment of sexual maturity (Pépin et al, 1987;Mauget & Pepin, 1991) or to those studies which accentuated the importance of body weight over age (Drimaj et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that wild boar males reached puberty at a similar age as the domestic pig, already in the first year of age, and so much earlier than common literature suggests. We also supposed that the body weight could drive the attainment of puberty much more efficient than a specific required age, as with regard to evidence in the human medicine (Blum et al, 1997;Aydin et al, 2017), adequate body energy reserves are essential to continue the reproductive development until sexual maturation.…”
Section: Introductionmentioning
confidence: 99%